2018
DOI: 10.4103/wjnm.wjnm_32_17
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography-computed tomography for inguinal nodes in vulvar cancer

Abstract: We aimed to determine the sensitivity and specificity of fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) for the spread of disease to inguinal lymph nodes in vulvar cancer. A retrospective review of vulvar cancer patients who underwent both inguinal nodal sampling and dissection as well as FDG PET-CT was performed, with 21 patients meeting criteria. The sensitivity and specificity of the FDG PET-CT imaging was performed using a combination of maximum standardized uptake value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Similar results were observed in the pelvis-based analysis. Previous PET or PET/CT studies showed variable results in terms of diagnostic performance, with sensitivity ranging from 50 to 100% and NPV from 57 to 100% for detecting metastatic LNs in vulvar cancer [12][13][14][15][16][17][18][19][20]. All these studies referred to small series (8-47 NMHP, non-metastatic with high probability; MHP, metastatic with high probability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were observed in the pelvis-based analysis. Previous PET or PET/CT studies showed variable results in terms of diagnostic performance, with sensitivity ranging from 50 to 100% and NPV from 57 to 100% for detecting metastatic LNs in vulvar cancer [12][13][14][15][16][17][18][19][20]. All these studies referred to small series (8-47 NMHP, non-metastatic with high probability; MHP, metastatic with high probability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessing the performance of [ 18 F]FDG-PET/CT mainly used qualitative assessment [ 12 – 14 , 17 ]. LN-SUV max values were reported only in few manuscripts [ 15 , 18 20 ]. In the current study, semi-quantitative analysis showed to be not superior to qualitative analysis, confirming our previous results in a small series of patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI, ultrasound with or without puncture of inguinofemoral lymph nodes, CT and PET/CT may be used to define the extent of tumour and/or for treatment planning [11,20,21,39,40].…”
Section: Diagnosis and Initial Stagingmentioning
confidence: 99%
“…Lymph node biopsy may be performed either by FNA or by core biopsy. There are no published data comparing the performance of these to puncture techniques in the clinical setting of vulvar cancer staging, and the wider available experience addressing this topic comes from breast cancer studies [36][37][38][39][40][41]. In the study of Solon et al [36], core biopsy of suspicious nodes showed a sensitivity rate of 96%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 64%.…”
Section: Diagnosis and Initial Stagingmentioning
confidence: 99%